A rare cause of gastrointestinal bleeding in the post-transplant setting - Bawane, Piyush; Jain, Mayank; Balkrishnan, Mahadevan; R, Ravi; Varghese, Joy; Venkataraman, Jayanthi; Vij, Mukul; Rela, Mohamed (Clinical and Experimental Hepatology, 2017)
Post-transplant lymphoproliferative disorder (PTLD) is a life-threatening complication noted after solid organ transplantation and is frequently related to Epstein-Barr virus infection. The present case highlights an unusual presentation of PTLD – gastrointestinal bleeding – in the absence of systemic symptoms.